"Coming out" among gay Latino and gay White men: implications of verbal disclosure for well-being. Issue 4 (3rd July 2016) - Villicana, Adrian J.; Delucio, Kevin; Biernat, Monica
Abstract: We examined how verbal disclosure affects subjective well-being among gay Latino and White men. In Study 1, increased gay identification predicted increased verbal disclosure for gay White men but not for gay Latino men, who reported verbal disclosure levels in line with a tacit coming out strategy (expressing one's sexual orientation to others more non-verbally) regardless of their gay identification. Moreover, low verbal disclosure hindered subjective well-being only for gay White men. In Study 2, we show that increased intrinsic self-expression and higher relational self-construal explained the positive relationship between verbal disclosure and well-being among gay White men. This mediational model did not hold for gay Latino men. We discuss verbal disclosure in relation to mainstream understandings of coming out.